PENGEMBANGAN MODUL AJAR MENULIS CERITA PANJI DENGAN STRATEGI METAKOGNITIF SMP KELAS VII - Moch. Muarifin; Endang Waryanti; Encil Puspitoningrum; Sherly Nur Azizah; Alfika Fatkhiyatul Ilma (Universitas Negeri Makassar, 2025)
This study aims to develop a teaching module for writing Panji stories based on metacognitive strategies for junior high school students in grade VII. This module is designed to improve students' creative writing skills while introducing local cultural values through Panji stories. The research used the Research and Development (R&D) method with four stages of development, namely define, design, develop and disseminate. The data collection technique in this study involved three steps, namely observation, interview, and validation questionnaire. While the data analysis technique in this research is quantitative descriptive. The results showed that the developed module was valid and relevant to the curriculum. Feedback from teachers and students indicated that the module helped students in understanding the story structure, developing characters, and conveying moral messages. The metacognitive strategy approach applied enabled students to plan, monitor, and evaluate the writing process. In addition, this module supports the development of 21st century skills, such as critical thinking, creativity, and collaboration, as well as utilizing information technology in learning.